2010
DOI: 10.1371/journal.pone.0011654
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Non-Selective Cation Channel TRPV4 Interaction with Cytoskeleton and Their Reciprocal Regulations in Cultured Cells

Abstract: BackgroundTRPV4 and the cellular cytoskeleton have each been reported to influence cellular mechanosensitive processes as well as the development of mechanical hyperalgesia. If and how TRPV4 interacts with the microtubule and actin cytoskeleton at a molecular and functional level is not known.Methodology and Principal FindingsWe investigated the interaction of TRPV4 with cytoskeletal components biochemically, cell biologically by observing morphological changes of DRG-neurons and DRG-neuron-derived F-11 cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 147 publications
(135 citation statements)
references
References 100 publications
5
130
0
Order By: Relevance
“…17 Indeed, MAP7, a microtubule binding protein and soluble tubulin as well as polymerized microtubule interact with TRPV4, especially at the C-terminal region of TRPV4. 18,19 In a similar manner, close proximity of TRPV4 and actin filaments has been demonstrated by using fluorescence resonance energy transfer (FRET). 20 As TRPV4 is involved in the Charcot-Marie-Tooth disease type 2 (CMT2), it suggests that TRPV4 is genetically linked with other genes that are also involved in the same disease and thus TRPV4 share a special genotype-phenotype correlation with these gene products.…”
Section: Naturally Occurring Trpv4 Mutants and Genetic Disordermentioning
confidence: 93%
See 1 more Smart Citation
“…17 Indeed, MAP7, a microtubule binding protein and soluble tubulin as well as polymerized microtubule interact with TRPV4, especially at the C-terminal region of TRPV4. 18,19 In a similar manner, close proximity of TRPV4 and actin filaments has been demonstrated by using fluorescence resonance energy transfer (FRET). 20 As TRPV4 is involved in the Charcot-Marie-Tooth disease type 2 (CMT2), it suggests that TRPV4 is genetically linked with other genes that are also involved in the same disease and thus TRPV4 share a special genotype-phenotype correlation with these gene products.…”
Section: Naturally Occurring Trpv4 Mutants and Genetic Disordermentioning
confidence: 93%
“…21 Indeed, our recent study confirmed that Neurofilament protein physically interacts with TRPV4. 19 In the same context, Kif1B, which is also involved in the CMT2 disease and/or peripheral neuropathic pain development, may A better and further understanding of TRPV4 structure, interaction and function can also be derived from studies that have generated and characterized several artificial TRPV4 mutations ( Table 2). All these mutations mostly alter single amino acids or cause deletion of specific regions.…”
Section: Naturally Occurring Trpv4 Mutants and Genetic Disordermentioning
confidence: 99%
“…Although chondrocyte [Ca 2+ ] i signaling exhibits a high sensitivity to variations in osmolarity or volume (41)(42)(43)(44), there is little or no sensitivity to physiologic levels of other physical stimuli, such as direct membrane stretch, suggesting that membrane connections to the pericellular matrix and/or intracellular cytoskeleton are important for the generation and transduction of [Ca 2+ ] i transients. TRPV4 has known physical interactions with both transmembrane proteins (integrins) (45,46) and cytoskeletal elements (microtubules, actin, tubulin) (47,48), and can transduce a diverse set of environmental signals (49). However, the complete Fig.…”
Section: Camentioning
confidence: 99%
“…12 Similarly, TRPV4 is also located at the filopodial and lamelipodial structures; 13 and in a same manner, endogenous TRPV4 is also present in the cholangiocyte cilia.…”
Section: Genetic Functional and Physical Interaction And Effect Of Mmentioning
confidence: 90%